The relationship between psychological capital and turnover intention: work engagement as mediator and work experience as moderator - Manish Gupta,; Musarrat Shaheen, (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study examines the mediating role of work engagement, and the moderating role of experience with the current organization, in the relationship between psychological capital and intention to turnover. The questionnaires was sent to a sample consist of 217 employees working in diverse industries in service sector. The results from Structural Equation Modeling indicate support for the mediating role of work enggagement, but not the moderating role of work experience. This suggests that psychological capital is a distant precursor of intention to turnover and affects it indirectly through work engagement. Practical implications and directions for future research have been discussed in detail.